Antineoplastic agents used in pediatric hematopoietic bone marrow transplantation: a review about pharmacology and pharmaceutical issues. - Barreto, Larissa Maria Hilsdorf Bernardi; Rodrigo Spineli Macedo; Ana Carolina Sayuri Nagai; Ananda Vial Cobello; Haíssa Pereira Ramos Rodrigues (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
This article proposes the characterization of the main chemotherapeutic agents used in hematopoietic stem cell transplantation in pediatric patients, carrying out a review of the main pharmacological and pharmacokinetic characteristics that are peculiar to children, as well as technical aspects for the handling, prescription, and administration of each one of these. It is extremely important that all professionals know how to recognize the characteristics of each drug and how its peculiarities impact the quality of patient's treatment, being able to predict and propose necessary interventions for potential problems of therapy, which can be identified and measured.